Perceived Organizational Support, Organizational Justice, and Psychological Capital: Their Impact on Organizational Citizenship Behavior Through Work Engagement - Gregorius Agusto Revo Gumbara; Aryana Satrya (Journal of Business, Social and Technology, 2026)
Background: The thermoforming manufacturing industry faces operational challenges related to resin price volatility, stringent quality requirements, and shift-based production coordination. Organizational Citizenship Behavior (OCB) can support operational effectiveness through voluntary employee contributions. Objective: This study examines the effects of Perceived Organizational Support (POS), Organizational Justice (OJ), and Psychological Capital (PsyCap) on OCB through Work Engagement (WE) among permanent production employees in thermoforming manufacturing companies. Methods: This study used a quantitative cross-sectional survey with structured questionnaires. Data were analyzed using Covariance-Based Structural Equation Modeling (CB-SEM) with the Robust Maximum Likelihood Satorra-Bentler estimator in LISREL 8.8. Results: POS, OJ, and PsyCap positively influenced WE. POS, OJ, PsyCap, and WE also positively influenced OCB. WE partially mediated the relationships between POS, OJ, PsyCap, and OCB. OJ had the strongest effect on WE, while WE had the strongest effect on OCB. Conclusion: Organizational support, organizational justice, psychological capital, and work engagement play important roles in strengthening OCB among thermoforming production employees. These findings indicate that organizational and pers onal resources can encourage voluntary extra-role behavior both directly and through greater work engagement.